2020
DOI: 10.1038/s41522-020-00163-7
|View full text |Cite
|
Sign up to set email alerts
|

The sino-nasal warzone: transcriptomic and genomic studies on sino-nasal aspergillosis in dogs

Abstract: We previously showed that each dog with chronic non-invasive sino-nasal aspergillosis (SNA) was infected with a single genotype of Aspergillus fumigatus. Here, we studied the transcriptome of this fungal pathogen and the canine host within the biofilm resulting from the infection. We describe here transcriptomes resulting from natural infections in animal species with A. fumigatus. The host transcriptome showed high expression of IL-8 and alarmins, uncontrolled inflammatory reaction and dysregulation of the Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…In the study of Bertuzzi et al [112] it was observed that the zinc transporter ZrfB (Afu2g03860) was downregulated under neutral-alkaline conditions via PacC (Afu3g11970), suggesting that A. fumigatus biofilms are neutral to alkaline. Interestingly, mature biofilms in dogs suffering from sino-nasal aspergillosis (SNA) have an elevated pH of around 8 [89]. In agreement with this, it was found that the ZrfC (Afu4g09560) zinc transporter was also expressed in biofilms in SNA, which is required for zinc acquisition under alkaline conditions [115].…”
Section: Transcriptomic Studies Of Biofilmsmentioning
confidence: 81%
See 2 more Smart Citations
“…In the study of Bertuzzi et al [112] it was observed that the zinc transporter ZrfB (Afu2g03860) was downregulated under neutral-alkaline conditions via PacC (Afu3g11970), suggesting that A. fumigatus biofilms are neutral to alkaline. Interestingly, mature biofilms in dogs suffering from sino-nasal aspergillosis (SNA) have an elevated pH of around 8 [89]. In agreement with this, it was found that the ZrfC (Afu4g09560) zinc transporter was also expressed in biofilms in SNA, which is required for zinc acquisition under alkaline conditions [115].…”
Section: Transcriptomic Studies Of Biofilmsmentioning
confidence: 81%
“…Gliotoxin, for example, is an important molecule in the regulation of the host response via several mechanisms, for example the induction of apoptosis in leukocytes and the inhibition of T-cell and B-cells response [107]. Interestingly, expression of the gliotoxin and hexadehydro-astechrome clusters was also detected in mature biofilms in dogs suffering from sino-nasal aspergillosis (SNA) [89], underscoring the important role of these secondary metabolites for A. fumigatus growing in biofilm.…”
Section: Transcriptomic Studies Of Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungal rhinitis secondary to infection with Aspergillus fumigatus is a common cause of nasal disease in dogs while it is uncommon in humans. Why young otherwise healthy dolichocephalic dogs have their nasal cavity and sinus invaded by the fungus is not yet totally understood, despite extensive investigation [13][14][15] . Local dysimmunity is suspected, which associates a host response, consisting in Th1 and in ammatory response 16,17 with an in-host adaptive genetic and phenotypic response of the fungus itself, enabling growth of the pathogen and contributing to the suppression of the host immune response 15,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Fungal rhinitis secondary to infection with Aspergillus fumigatus is a common cause of nasal disease in dogs while it is uncommon in humans. Why young otherwise healthy dolichocephalic dogs have their nasal cavity and sinus invaded by the fungus is not yet totally understood, despite extensive investigation [ 13 15 ]. The host itself but also the fungus have been described as contributing to local dysimmunity.…”
Section: Introductionmentioning
confidence: 99%